Aplikasi Agens Hayati dan Humus untuk Menekan Populasi Fusarium oxysporum f.sp. cubense Penyebab Busuk Batang Pisang - NI KADEK LIA SWANDEWI; I MADE SUDANA; I KETUT SUADA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
Application of Biological Agent and Humus to Suppress Population Fusariumoxysporum f.sp. cubense the Cause of Banana Stem Rot. The study aimed to determine the interaction between P. fluorescens, Trichoderma spp. fungus, and humus in suppressing the population of Fusariumoxysporum f.sp. cubense in the soil. The design used was a randomized blockdesign (RBD) of 2 factors namely antagonistic microbes and humus. There were 18treatments with 3 replications so that 54 experimental units were obtained. Thevariables observed were the population of Foc, population of P. fluorescens,population of Trichoderma spp., and soil pH. The results showed that thecombination of biological agent and humus could reduce the population of Foc. Thehigher concentration of humus combined with biological agent showed thedecreasing population of Foc which causes rot of banana stems.